Validasi Metode Pengukuran Kadar Total Flavonoid dalam Ekstrak Etanol Sirih Merah (Piper crocatum var. Ruiz & Pav) Menggunakan Nano Spektrofotometer BMG Lab. Tech. - Hudayanti, Martini; Sarah, Elitawati; Kurniatin, Popi Asri (Jurnal Pengelolaan Laboratorium Pendidikan, 2025)
Method validation is a crucial step when an analytical method is applied using different instruments to ensure the accuracy, precision, and reliability of the results. This study aimed to validate the method for determining the total flavonoid content in the 70% ethanol extract of red betel leaves (Piper crocatum) using a BMG LAB.TECH nanospectrophotometer equipped with a 96-well plate. This method offers advantages in terms of time efficiency and sample volume compared to conventional spectrophotometric techniques. The validation parameters assessed included linearity, precision, accuracy, limit of detection (LoD), and limit of quantitation (LoQ). The results demonstrated excellent linearity with a correlation coefficient (r) of 0.997. Precision testing yielded a relative standard deviation (%RSD) of 2.65%, while accuracy testing showed an average recovery rate of 104.33%. The LoD and LoQ were calculated to be 4.06 ppm and 13.52 ppm, respectively. Based on these findings, the total flavonoid content in the ethanol extract of the red betel leaves was determined to be 24.30 mg QE/g. Because the method meets the validation criteria outlined in the ICH guidelines, it is considered valid and suitable for use in educational laboratory activities and scientific research applications.